Patient-derived organoids can predict response to chemotherapy in metastatic colorectal cancer patients - Ooft, Salo N; Weeber, Fleur; Dijkstra, Krijn K; McLean, Chelsea M; Kaing, Sovann; van Werkhoven, Erik; Schipper, Luuk; Hoes, Louisa; Vis, Daniel J; van de Haar, Joris; Prevoo, Warner; Snaebjornsson, Petur; et al. (Science translational medicine, 2019)
There is a clear and unmet clinical need for biomarkers to predict responsiveness to chemotherapy for cancer. We developed an in vitro test based on patient-derived tumor organoids (PDOs) from metastatic lesions to identify nonresponders to standard-of-care chemotherapy in colorectal cancer (CRC). In a prospective clinical study, we show the feasibility of generating and testing PDOs for evaluation of sensitivity to chemotherapy. Our PDO test predicted response of the biopsied lesion in more than 80% of patients treated with irinotecan-based therapies without misclassifying patients who would have benefited from treatment. This correlation was specific to irinotecan-based chemotherapy, however, and the PDOs failed to predict outcome for treatment with 5-fluorouracil plus oxaliplatin. Our data suggest that PDOs could be used to prevent cancer patients from undergoing ineffective irinotecan-based chemotherapy.